Towards a new socialism - Anton , Anatole (ed.); Schmitt , Richard (ed.) (London, 2007)
Toward a New Socialism offers a critical analysis of capitalism's failings and the imminent need for socialism as an alternative form of government. This book demonstrates that capitalism is destructive and limiting to the many ongoing campaigns to increase freedom, equality, and security. Anatole Anton and Richard Schmitt join together to compile a volume of essays exploring the benefits and consequences of a socialist system as an avenue of increased human solidarity and ethical principle. The essays offer a new definition of socialism by investigating its theories and principles, influence on social institutions, and role in work dynamics. Raising important and unavoidable questions for contemporary society. Toward a New Socialism is a vital resource for scholars of political theory and the globalization movement, as well as a necessary read for every
Keywords: Socialism